Dynamic Capabilities and Core Competencies in Achieving Competitive Advantage of Agroforesty-Based School - Nur Choirul Afif; Wahyudin Wahyudin (Universitas Negeri Makassar, 2020)
This research purposes to prove whether a school not standard in the learning process or having unique resources is able to compete with general schools, which are in accordance with national standard of education in Indonesia. The results of this study showed that dynamic capabilities had a positive effect on core competencies in the agroforestry-based school. Dynamic capabilities did not affect competitive advantage in the agroforestry-based school. Core competencies had a positive effect on competitive advantage in the agroforestry-based school. Core competencies mediated the effect of dynamic capabilities on competitive advantage in the agroforestry-based school. Thus, resource capabilities should be able to form core competencies in educational institutions in order to be able to create competitive advantage for graduates of this school.